Pencegahan Kurang Energi Kronik pada Ibu Hamil melalui Edukasi dan Pelatihan Kader Kesehatan di Desa Buntuna, Tolitoli - Hasni Hasni; Alfrida Semuel Ra'bung; Saman Saman; Sova Evie; Novica Arianti Putri; Dwi Yogyo Suswinarto; Rahmat Kurniawan; Azwar Azwar (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Chronic Energy Deficiency (CED) in pregnant women remains a serious public health challenge due to its impact on both maternal and fetal health, ranging from delivery complications and anemia to the risk of low birth weight (LBW) and stunting. Data from the Tolitoli District Health Office in 2023 reported 406 cases of CED among pregnant women, with the highest prevalence (19.2%) found in Baolan Subdistrict. This condition highlights the need to strengthen the role of community health cadres in early detection and nutritional support for pregnant women. This Community Service Program aimed to improve cadres’ knowledge and skills in monitoring maternal nutritional status through simple anthropometric measurements (Mid-Upper Arm Circumference, body weight, and height). The activity was conducted in Buntuna Village, within the working area of Baolan Health Center, Tolitoli District, on July 30, 2025, involving 18 health cadres. The methods included education using presentations and booklets, a question-and-answer session, and hands-on practice of anthropometric measurements. Knowledge was assessed using pre- and post-tests with questionnaires, while skills were observed using a checklist-based assessment. The post-test results indicated a significant improvement in knowledge from 40% to 86%, while skills increased from 11% to 100%. Prior to the intervention, only two cadres were skilled, but after training, all participants were able to perform measurements accurately. These findings demonstrate that practice-based training is effective in strengthening cadre capacity and has the potential to enhance the effectiveness of CED prevention programs at the community level.